Geohistory of the Makassar Spice Network from the 16th to 17th Century - Rifal (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2024)
Abstract: This article discusses the geohistory of the spice network of Makassar from the 16th to the 17th century. The modern world of eastern Indonesia, including Makassar, is thought to have begun after the arrival of foreigners. This needs to be re-examined, as the trade of the inland kingdoms played an important role in the development of the coastal kingdoms. Makassar's trade had contacts with Banda. For this reason, the author presents a geohistorical study of the natural formation of a spice trade network in the interior of South Sulawesi. The purpose of this study is to reveal the role of geography, topography, surrounding islands, marine systems, climate and munsom winds, both on the west coast of Sulawesi, the east coast of Sulawesi and the mountains, in the development of the spice network in Makassar. The method used in this study is the historical research method with a literature approach. As described by Kuntowijoyo, from the selection of topic, heuristics, verification, interpretation and historical writing. The literature review study has an important position in revealing the problem. The results show that the development of Makassar's spice network cannot be separated from the geographical conditions, topography, surrounding islands, marine systems, climate and Munsom winds. In addition, Makassar is located on the main sea route connecting a number of sea systems (Makassar Strait, Bone Bay, Flores Sea, Banda Sea and Java Sea). With such a geostrategic structure, the kingdoms of the hinterland. Abstrak: Artikel ini membahas geohistori jaringan rempah Makassar abad XVI-XVII. Dunia modern Indonesia Timur termasuk Makassar dianggap dimulai setelah masuknya bangsa asing. Hal tersebut perlu ditelaah ulang, mengingat bahwa perdagangan kerajaan pedalaman memiliki peran penting dalam perkembangan kerajaan-kerajaan pesisir. Perdagangan Makassar telah memiliki kontak dagang dengan wilayah di Banda. Untuk itu penulis mengetengahkan kajian geohistori yang terbentuk secara alamiah yang membentuk jaringan perdagangan rempah di pedalaman Sulawesi bagian selatan. Tujuan penelitian ini mengungkap peranan geografis, topografi, pulau-pulau sekitarnya, sistem laut, iklim dan angin munsom, baik yang terletak di pantai barat Sulawesi, pantai timur Sulawesi, serta pegunungan dalam perkembangan jaringan rempah di Makassar. Metode yang digunakan studi ini, metode penelitian sejarah dengan pendekatan kepustakaan. Sesuai yang dijabarkan Kuntowijoyo, mulai dari memilih topik, heuristik, verifikasi, interpretasi, dan penulisan sejarah. Studi literature review memiliki posisi penting dalam mengungkap masalah. Hasil penelitian menujukkan perkembangan jaringan rempah Makassar tidak dapat dilepaskan dari kondisi geografis, topografi, pulau-pulau sekitarnya, sistem laut, iklim dan angin munsom. Selain itu Makassar terletak di jalan utama maritim yang menghubungkan sejumlah sistem laut (Selat Makassar, Teluk Bone, Laut Flores, Laut Banda, dan Laut Jawa). Dengan struktur geostrategis, kerajaan-kerajaan pedalaman sebagai penghasil beras dibarter dengan rempah-rempah